Glyphosate Herbicide Use in Urochloa brizantha Management in Intercropping With Herbicide-Resistant Maize - SILVA,D.V. (2016)
The success of the intercropping among cultivated species depends on the adoption of practices that provide, in due course, greater competitive ability of a species over another. The objective of this study was to evaluate the use of glyphosate herbicide in the suppression of Brachiaria (signalgrass) intercropped with maize. The experiment was conducted in a randomized complete block design with four replications. The treatments were arranged in a 5 x 2 + 2 factorial arrangement, the first factor corresponding to the doses of glyphosate (48, 96, 144, 240, 480 g ha-1 of the acid equivalent (a.e)) and the second one to the vegetative stages of the signalgrass at the time of application (2 and 4 tillers). Two controls were added to the treatment list, comprising controls without herbicide application and hand removal of the signalgrass. The number of plants, tillers and dry matter of signalgrass was reduced with glyphosate. The increase of the glyphosate doses enhanced the injure to the forage plants, mainly when the compound was sprayed at the two-tiller vegetative stage. The dry matter of maize plants increased proportionally to the glyphosate dose. However, the height of the maize plants was not affected. The grain mass and productivity of maize grain increased with increasing dose of glyphosate. The maize yield was negatively influenced on the untreated control. Glyphosate at 96 and 144 g ha-1, when applied at 2 and 4 tiller stage, respectively, reduces the growth of signalgrass and does not affect the maize grain yield.